A metáfora da água na poesia de Graça Pires : memória, infância e solidão - (:unkn) unknown (Universidade Estadual de Goiás, 2020)
This dissertation’s goal is to analyze the water metaphor in Graça Pires’s poetry, Contemporary Portuguese author whose writing remakes, through memories, her childhood and loneliness paths by adopting Nature as a reference. The water element, which is a constant presence in the author’s work, symbolizes life, fluidity of things and the concerns of the being. These topics are examined with the theoretical contribution of Gaston Bachelard (1988; 1993; 1997), Hugo Friedrich (1991), Octávio Paz (1984; 1993; 2012) and Raíssa Cavalcanti (1999), among others whose presupposes compose the textual tessiture about the raw material of the poem: lyricism, aesthetic language, self-contemplation and the sacredness of water as an element of creation and sustaining life. In addition to that, based on this theoretical foundation, we seek to establish a relation between the poems we analyze and the water element, taken as a key index of poetic creation by the author. Finally, the analysis will unfold over the poetic work of Graça Pires, situated and built from the semantics of water linked to the meanings of freedom and loneliness before the poetic experience of the lyrical subject of the text. This movement, which is constituted in language in an existential condition connected to her childhood memories, loves stories and loneliness, reflects and shows the actions of human being in the 21st century, as indexes that form her poetry.
Keywords: Metáfora da Água; Solidão; Memória; Infância; Natureza; Water metaphor; Loneliness; Memory; Childhood; Nature; LINGUISTICA, LETRAS E ARTES